The Influence of Parents' Socioeconomic Status on the Learning Outcomes of Grade XI Students of State Preparatory Madrasah Aliyah 4 - Nadia Armyliyanda; Hendri Fauza; Ripho Delzy Perkasa (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to describe and analyze the extent to which the influence of the socio-economic status of parents on the learning outcomes of class students. The research method uses quantitative research with a descriptive correlative approach implemented at Madrasah Aliyah Persiapan Negeri 4 Medan. The population in this study were all students of class XI with a sample of 168 students. The data analysis technique in this study used a prerequisite test consisting of a normality test, a homogeneity test, a linearity test, and a multicollinearity test. Then continued with a hypothesis test consisting of a partial test (t test), a simultaneous test (F), multiple linear regression analysis, a determination coefficient test (R2) and a correlation coefficient test. The results showed that in the education level coefficient, the Tcount value <Ttable is 0.804 <1.97462, so H0 is accepted and Ha is rejected. This means that there is no influence of the level of parental education on student learning outcomes. In the income level coefficient, the Tcount value> Ttable is 2.348 <1.97462, so Ha is accepted and H0 is rejected. This means that there is an influence of parental income level on student learning outcomes. While in the work coefficient, the Tcount value <Ttable is -1.616 <1.97462, so Ha is accepted and H0 is rejected. This means that there is no influence of parental work on student learning outcomes. Then the probability value of significance (sig) <0.05 is obtained, namely 0.044 <0.05 and the Fcount value> Ftable is 2.762> 2.66, so Ha is accepted and H0 is rejected. So it is obtained that there is an influence of parental socio-economic status on learning outcomes which can be shown from the value of the determinant coefficient (R square) of 0.048, meaning that the influence of the socio-economic status variable on learning outcomes is 0.048 or 4.8%. While the correlation value (R) is 0.220 or 22% which indicates a low level of relationship. From the above understanding, it can be concluded that there is an influence of parental socio-economic status on student learning outcomes (Ha is accepted and H0 is rejected).